Pemberdayaan Komunitas UMKM Gayatri Mahardika Melalui Optimalisasi Pemasaran Digital dan E-Commerce di Era New Normal - Fauzan Aziz; Retno Setyorini; Dewi K. Soedarsono; Agus Maolana Hidayat; Kristina Sisilia; Robbi Hendriyanto; Wardani Muhamad; Anak Agung Gde Agung; Kristina Sisilia (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Digital MSMEs are one of the important elements in supporting the national economy as a whole where the government encourages economic growth by empowering MSMEs towards Go-Digital in Indonesia. This role is predominantly carried out by the economic industry in the process of creating and growing various types of MSMEs, including digital MSMEs. The private sector, be it profit-oriented or non-profit organizations, also took part in supporting the MSME program. The Gayatri Mahardika MSME community as a non-profit organization that has an MSME development program towards Go-digital has problems in business introduction and digital marketing which is still done manually and uses tools that are commonly used for business introduction using word-of-mouth information dissemination systems and conventional digital marketing. It is, considered ineffective and efficient. They need digital marketing solutions, both to expand the market, including to survive the pandemic. Gayatri Mahardika MSME Community Empowerment Solution Through Optimization of Digital Marketing and E-commerce in the New Normal Era is expected to increase knowledge and knowledge about digital marketing and can improve the marketing system of every MSME in the Gayatri Mahardika Community so that it can survive during the pandemic and develop more so that it can improve income profits.